Neke društvene prepreke rodnoj jednakosti u Hrvatskoj - Galić, Branka (2005)
Although we accept and respect building of the legislational framework as the important and necessary tool for achieving (formal) gender equality, we do not have any illusions of its being a sufficient condition for the implementation of gender equality in our Croatian society without being honest in changing social prerequisites in order to be achieving it, which is to lead us from traditional and "premodern" patriarchal values to "modern/postmodern" value system - including egalitarian distribution of all (though perhaps scarce) social resources and particularly all social and institutional relations. There are two dimensions which characterise our society as the two main origins of creating and persisting of patriarchal values in Croatia: A) traditional (patriarchal) religious identity - based on confessional affiliation, believing in fundamental principles of the dominant religion (Christianity) and the religious practice, and B) sexist discourse of gender identity - based on the exclusive gender socialisation and gender-work differentiation.
Projekt MZOS
ENG